Integrasi, Implementasi, dan Evaluasi Pengendalian Mutu dalam Manajemen Modern - Jumawati, Jumawati; Ramli, Rosmiati; Sukriati, Sukriati; Hamran, Hamran; Ahmad, Muhammad Ikhwan; Imran, Muhammad Afit; Saleh, Abd. Rahman (Sulawesi Tenggara Educational Journal, 2025)
Quality control has become an important aspect of modern management, with the aim of ensuring that products or services meet the established standards. This article examines various literatures related to the integration, implementation, and evaluation of quality control in the context of modern management. This literature review aims to explore current approaches in managing quality within organizations, as well as the role of quality control in improving operational efficiency and customer satisfaction. In the context of modern management, quality control is not only focused on technical aspects but also involves the participation of all organizational elements, from top managers to field employees. The study also discusses various models and tools of quality control, such as Total Quality Management (TQM) and Six Sigma, and how these two approaches are applied in various industrial sectors. The findings suggest that the integration of effective quality control requires commitment from all levels of the organization, along with clear evaluation mechanisms to ensure the successful implementation of quality control. This research provides insights into the importance of quality control in creating sustainable competitive advantages in the era of modern management